Modernization of Management System of Higher Education Institutions: An Empirical Perspective from Uzbekistan - Hakimova Muhabbat; Shaturaev Jakhongir; Turabekov Farxod; Khakimova Khulkar (Indonesian Journal of Multidiciplinary Research, 2023)
Nobody doubts the inefficiency and inadequacy of the modern system of higher education management, but the proposed approaches to its modernization are extremely ambiguous. Our solution to this important problem is rather original and unique. The system of management in the field of higher education can be attributed more to a centralized model with certain sprouts, which form the transition to a decentralized form. To speed up this process, we consider it necessary to form more perfect control systems based on network communications. We tried to identify the modernization drivers of the management system of higher education institutions in Uzbekistan, thus we selected three higher education institutions. 600 students, lecturers, and leaders in total were involved in the research observation. The result of the empirical research demonstrated a slight growth in quality assurance and knowledge management in the teaching-learning process and research affairs of the universities, however, there are still many areas yet to get covered or ill equipped.